The Effect of Return on Assets (ROA), Debt to Equity Ratio (DER), Earning Per Share (EPS) on Company Value in Mining Sector Companies Listed on the BEI Period (2018 - 2022) - Elfiza Abbas, Yeni; Anicetus, A.; Ana, Sri; Gustiawan, Deni (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study aims to determine the effect of Return on Assets (ROA), Debt to Equity Ratio (DER), and Earning Per Share (EPS) on the value of mining sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2018. -2022. The companies sampled were 8 (eight) companies through purposive sampling which involved selecting samples based on criteria as mining sector companies listed on the Indonesia Stock Exchange 2018-2022, and did not experience losses during the study period. The method used in this research is panel data regression analysis using Smart-PLS 4 software. The results showed that DER has a significant effect on Firm Value in this case Price to Book Value (PBV) as an indicator of firm value, while EPS has a low effect on Price to book value (PBV), and Return on Assets has no significant effect on Price to Book Value (PBV). This information is very important for managers and investors to understand the factors that affect business performance in the mining sector.